2012
DOI: 10.1103/physreva.85.022340
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical decoupling in optical fibers: Preserving polarization qubits from birefringent dephasing

Abstract: One of the major challenges in quantum computation has been to preserve the coherence of a quantum system against dephasing effects of the environment. The information stored in photon polarization, for example, is quickly lost due to such dephasing, and it is crucial to preserve the input states when one tries to transmit quantum information encoded in the photons through a communication channel. We propose a dynamical decoupling sequence to protect photonic qubits from dephasing by integrating wave plates in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A technique for minimizing the quantum noise is called dynamical decoupling. The application of dynamical decoupling in an optical fiber to reduce quantum noise was first proposed by Wu and Lidar in [22], and later investigated in [23][24][25][26][27] for the protection of photonic qubits traveling in an optical fiber. Although dynamical decoupling has been used to preserve the state of a qubit, it has never been applied for reduction of noise in an AC signal in an optical fiber.…”
Section: Optical Magnetometerymentioning
confidence: 99%
See 2 more Smart Citations
“…A technique for minimizing the quantum noise is called dynamical decoupling. The application of dynamical decoupling in an optical fiber to reduce quantum noise was first proposed by Wu and Lidar in [22], and later investigated in [23][24][25][26][27] for the protection of photonic qubits traveling in an optical fiber. Although dynamical decoupling has been used to preserve the state of a qubit, it has never been applied for reduction of noise in an AC signal in an optical fiber.…”
Section: Optical Magnetometerymentioning
confidence: 99%
“…If a photonic qubit propagates for a length ∆L in an optical fiber then the phase accumulated by it is given by ∆φ = (2π/λ)∆L∆n, where ∆n is the birefringence of the fiber and λ is the wavelength. We model the axially varying index dephasing in an optical fiber of length L by a series of concatenated, homogeneous segments of length ∆L with constant ∆n [23,26,31]. The index fluctuations across these segments of fiber are random and the stochastic fluctuation of refractive index difference ∆n(x) across the segments are simulated as a Gaussian-distributed zero mean random process [31,32].…”
Section: Noise Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…M z is the noise operator and B z is the bath operator that couples the polarization qubit to the noise bath and causes decoherence. To decouple the system from the environment, we introduce time-dependent perturbing Hamiltonian which rotates the qubit around a given axis on the Bloch sphere [14,21]. The interaction Hamiltonian with added perturbation is given as…”
Section: Dynamical Decouplingmentioning
confidence: 99%
“…In our previous work, we proposed the Carr-Purcell-Meiboom-Gill (CPMG) DD pulse sequence for preserving polarization qubit in a polarization-maintaining fiber where the birefringence of the fiber was simulated as a Gaussiandistributed, zero-mean random process [20]. We numerically showed that effect of decoherence can be minimized with the use of ideal pulses implemented using suitability oriented half-wave plates (HWP) and a fidelity greater than 99% can be achieved [21].…”
Section: Introductionmentioning
confidence: 99%